Resuscitation, yes or no ? the criteria for transferring patients with hematological malignancies to intensive care. A qualitative study - Violaine Bordier; Marilène Filbet; Corinne Sissoix; Colombe Tricou; Bruno Pereira; Virginie Guastella (BMC Palliative Care)
Abstract Background Having a hematological malignancy increases the risk of a poor-quality end of life and of dying in intensive care. There is no prognostic score to predict survival on admission to intensive care, but many patients die there. To identify the criteria used in deciding to transfer patients with hematological malignancies to intensive care. Methods It is a qualitative study. For each patient with a hematological malignancy who died in intensive care, the resuscitator and hematologist involved in the decision to transfer the patient to intensive care were contacted. The study ran at Lyon Sud Hospital Center, between 1 November 2018 and 30 April 2019. Semi-structured interviews were conducted with data triangulation. Seventeen doctors were contacted, and 17 interviews were conducted. Results When transferring a patient with a hematological malignancy to intensive care, we identified (i) patient-specific decision criteria for the transfer, namely prognosis of the disease and treatments received, and (ii) decision criteria specific to hematologists and resuscitators, namely difficulty confronting management failure, convenience of transfer to the ICU for hematologists, and attachment of hematologists to their patients. Conclusion Organizational convenience of transfer to intensive care was the main criterion for hematologists, but emotional attachment favored futile obstinacy, doing everything possible to the detriment of the patient’s comfort. It would be useful to make an upstream appraisal of the impact that an early evaluation of the level of care of patients with hematological malignancies could have on reducing deaths in intensive care.